Application Areas of Fuel Cells - Bayrak, Zehra Ural; Gencoglu, Muhsin Tunay (Ieee, 2013)
In the recent years there is an increasing interest in fuel cell technology and fuel cells have reached a high development status. This development was mostly advanced by the automotive industry and residential applications, because fuel cells are suitable to substitute the fossil fuels and also to provide an environment friendly propulsion. But there is also a growing market for stationary fuel cell applications (cogeneration of heat and power, and as a substitute for batteries in portable devices). In this study, application areas of the fuel cells were classified and investigated separately. In addition to the last developments and trend on the fuel cell technology were analyzed. Otherwise, the new application areas of the fuel cells were discove red and then economic advantages which usage of the fuel cell will provide were disputed.
International Conference on Renewable Energy Research and Applications (ICRERA) -- OCT 20-23, 2013 -- Madrid, SPAIN
Keywords: fuel cell; staionary; residential; distributed power; transportation; portable; space